The Effect of Weathered Layer Thickness and Slope on Potential Areas of Landslides in Gerbosari Village, Samigaluh District, Kulonprogo Regency, Indonesia - Novia Nurul Khayati; Sudarmaji; Eddy Hartantyo (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
Gerbosari Village has a history of landslides with intensity and risk of 56 occurrences over 5 years. Gerbosari Village, Samigaluh District, Kulonprogo Regency is located at geographic coordinates 7◦ 38 '45.33 "- 7◦ 41' 35.24" LS and 100◦ 9 '20.80 "- 110◦ 11' 16.52" BT with topographic conditions at an altitude around 500 - 1000 mdpl. This study aims to determine the subsurface structure of landslide-prone areas in the form of weathered layer thickness and the effect of slope in landslide-prone areas so that it can be used in making micro zonation maps of landslide-prone areas. This study uses 43 microtremor data with a distance between points of 650 m. The microtremor signal was analysed using the horizontal to vertical spectrum ratio ( HVSR) method. From the measurement results, it is obtained that the value of the dominant frequency ranges from 1 - 22 Hz, the value of the amplification factor is obtained in the range of 1 - 10.5, the value of the peak ground acceleration ranges from 60 - 300 cm/s2, the thickness of the weathered layer is obtained in the range of 12 - 22 meters. Based on the results of the slope analysis, the study area is on a slope classified as a bit steep - very steep.